The Influence of Leadership, Organizational Communication, Motivation and Work Discipline on the Performance of Principals in Junior High Schools in Central Bangka Regency - Iskandar, Iskandar; Lian, Bukman; Mahasir, Mahasir (Yayasan Sembilan Pemuda Indonesia, 2024)
The aim of this research is to determine and analyze the influence of leadership, communication, motivation and work discipline on the performance of principals in junior high schools throughout Central Bangka Regency. The sample consisted of 221 public and private middle school teachers. Data collection techniques included questionnaire methods and documentation, which involved collecting information from various sources such as notes, transcripts, books, and meeting minutes. The study reveals that leadership, organizational communication, motivation, and work discipline significantly impact the performance of Junior High School principals in Central Bangka Regency. Leadership positively influences the performance of principals, while organizational communication positively impacts their performance. Motivation positively influences the performance of principals, and work discipline influences their performance. Overall, these variables positively influence the performance of principals in Central Bangka Regency.